Determinación de los niveles de glicemia en pacientes adultos mayores de 65 a 85 años que acuden al hospital de Arenillas , cantón Arenillas durante el periodo 2014. - Morocho Medina, Gabriela (2015)
This research at the clinical laboratory, it aims to determine blood sugar levels in elderly patients aged 65 to 85 who come to the for the period 2014.The research sample was blood of elderly patients aged 65 at 85 years, which allowed us to relate the levels of glucose in patients with biochemical test.